1992
DOI: 10.1073/pnas.89.7.3000
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoplasmic localization of prelamin A: implications for prenylation-dependent lamin A assembly into the nuclear lamina.

Abstract: The synthesis of the nuclear lamina protein lamin A requires the prenylation-dependent processing of its precursor protein, prelamin A. Unlike p2lr", which undergoes similar initial posttranslational modifications, maturation of lamin A results in the proteolytic removal of the prenylated portion of the molecule. We have used an in vitro prenylation system to demonstrate the nature of the prenyl substituent on prelamin A to be a farnesyl group. Further, the in vitro farnesylation of prelamin A requires an inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
150
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(159 citation statements)
references
References 39 publications
8
150
1
Order By: Relevance
“…Our data reconciles the paradox surrounding nuclear lamin A processing, and indicates that the nucleus is a CaaXprocessing compartment, in addition to the ER membrane where Ras, Rho, a-factor, and other CaaX proteins are known to be modified (Gelb et al, 2006;Wright and Philips, 2006). Our findings provide a mechanistic and logistical basis for earlier evidence suggesting that the nuclear import of prelamin A via its strong NLS precedes its processing (Lehner et al, 1986;Lutz et al, 1992;Sasseville and Raymond, 1995). Confirmation of nuclear processing of lamin A also significantly impacts speculation of the as-yet-undetermined fate of the lamin A tail that is released by Zmpste24-mediated endoproteolytic cleavage ( Figure 1A, step 4).…”
supporting
confidence: 66%
See 4 more Smart Citations
“…Our data reconciles the paradox surrounding nuclear lamin A processing, and indicates that the nucleus is a CaaXprocessing compartment, in addition to the ER membrane where Ras, Rho, a-factor, and other CaaX proteins are known to be modified (Gelb et al, 2006;Wright and Philips, 2006). Our findings provide a mechanistic and logistical basis for earlier evidence suggesting that the nuclear import of prelamin A via its strong NLS precedes its processing (Lehner et al, 1986;Lutz et al, 1992;Sasseville and Raymond, 1995). Confirmation of nuclear processing of lamin A also significantly impacts speculation of the as-yet-undetermined fate of the lamin A tail that is released by Zmpste24-mediated endoproteolytic cleavage ( Figure 1A, step 4).…”
supporting
confidence: 66%
“…Early evidence had suggested that prelamin A is processed within the nucleus (Lehner et al, 1986;Beck et al, 1990;Goldman et al, 1992;Lutz et al, 1992;Sasseville and Raymond, 1995). However, the postprenylation CaaX-processing enzymes Icmt, Zmpste24, and possibly Rce1 are known to be integral membrane ER-resident proteins with their active sites facing the cytosol, suggesting that prelamin A could be processed before nuclear import Schmidt et al, 1998;Corrigan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations